RANCANG BANGUN JARINGAN WIRELESS LAN DAN INTERNET BERBASIS CLOUD PADA UNIVERSITAS BINA BANGSA GETSEMPENA - Satrio Danuasmo; Nazuarsyah Nazuarsyah; Rossiana Br Ginting (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2023)
The internet is now a part of our lives. Where to create an infrastructure that requires a design, analysis, and implementation to build a network that has comfort, security, and high reliability. Universitas Bina Bangsa Getsempena (UBBG) requires an internet infrastructure network that can be used for high mobility. UBBG builds a network in stages, which emphasizes the level of need for the academic community. In designing this network, it is determined the budget plan provided by the University regarding infrastructure development in the campus environment. In the first phase of this design, the focus is on Wireless Fidelity (Wi-Fi) access, internet access in laboratories, and University Local Area Network (LAN) networks. The results of this study are the effectiveness of network use, the number of connected clients, and the amount of traffic usage